Agrobiodiversidade em quintais agroflorestais indígenas Tikuna no município de Benjamim Constant-AM, fronteira Brasil-Peru-Colômbia - Rozendo, Max Francisco (Brasil, 2024)
Agroforestry Yards (AYs) can be characterised as agroecosystems where different plant species, both native and cultivated, are managed in a consortium or successional manner, and may also be associated with small domestic animal husbandry around the homes. For the Tikuna people and the families of the Philadelphia indigenous community in Benjamin Constant-AM, in the Alto Solimões, these spaces are generally known as terreiros. In the indigenous Tikuna language, AYs are traditionally conceptualised as Íãtü. Thus, this the aim of this study was to analyse ecological, productive and socio-economic aspects related to agrobiodiversity, in two agroforestry backyards in the indigenous community of Filadélfia, in the municipality of Benjamin Constant-AM, in the municipality of Benjamin Constant-AM, in the Alto Solimões micro-region, in the Brazilian Amazon. To this end, we opted for an exploratory, participatory, self-narrative, descriptive and qualitative case study. In yard I, the Silva family identified 40 and in yard II, the Rozendo family identified 25 plant species. Fruit trees and medicinal plants were prevalent in both backyards. The presence of animals, particularly birds, was dominant in both agroecosystems investigated. It was possible to observe that as well as providing a wide variety of food for both the family and the community, the Tikuna AYs also play a crucial role in preserving natural resources and maintaining local ecosystems. It was found that the two backyards are also responsible for relevant ecosystem functions and services, especially in terms of food provision and climate regulation. Thus, it is clear that the AYs investigated contribute significantly to the food and nutritional security of their maintainers, favour the conservation of agrobiodiversity in situ/on farm through the use and management practices of the plant species present in these agroecosystems and provide medicinal resources. The management of domestic animals also favours the families' diet. Knowing the importance of the AYs, especially Benjamin Constant-AM and the indigenous communities of the Alto Solimões, further studies are recommended in order to expand knowledge about these agroecosystems